Tantangan Dalam Implementasi Kekayaan Intelektual Sebagai Jaminan Pembiayaan Berdasarkan Peraturan Pemerintah Nomor 24 Tahun 2022 - Husny, Tengku Habib Ihza (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The regulation of intellectual property as collateral is not something new in Indonesia, especially in terms of copyrights or patents. However, it is difficult to implement because there are still legal obstacles. The government enacted Government Regulation Number 24 of 2022 which strengthens intellectual property provisions as collateral. This collateral is carried out in the form of a fiduciary guarantee in addition to contracts for creative economic activities or collection rights. This regulation allows creative economy actors to guarantee their intellectual property to obtain alternative sources of funding in developing their businesses. Even so, there are still challenges in implementing intellectual property as collateral. This study uses a doctrinal legal research method through a qualitative approach by utilizing secondary data as the main data based on a literature research. Sources of research data are laws and regulations, theories and relevant legal concepts. Data were analyzed using qualitative juridical methods and logical deductive reasoning. The results of the study show that there are still challenges in the implementation of intellectual property as collateral for financing such as the problem of valuing intellectual property assets, the existence of intellectual property appraisal institutions, the absence of a secondary market to trade intellectual property assets, and the problem of piracy that still occurs frequently.